A Substitution-Box Structure Based on Crowd Supply Infinite Noise TRNG - Ibrahim, Habib; Ozkaynak, Fatih (Ieee, 2021)
Practical applications in cryptology science have a very wide spectrum. One of the important primitives based on many of these applications is the substitution-box structures. Since substitution-box structures are the main component targeted by many attacks, developing new substitution-box structures resistant to new attack is a hot research topic. Random selection-based designs have become increasingly popular recently, as they are more resistant to side channel attacks than mathematically based designs. In this study, a random selection-based substitution-box structure is proposed. The proposed substitution-box is designed based on a true random number generator hardware. Analysis results showed that the proposed substitution-box has better performance criteria than many designs in the literature. These successful results indicate that the outputs of study can be used successfully in many practical applications that will be designed in the future.
9th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 28-29, 2021 -- Firat Univ, Elazig, TURKEY
Keywords: cryptography; substitution-box; random number generator; physical entropy source